Madrasa au Amrīkā - Armān, Samīʿ-ad-Dīn (D́ast́ Ān Buks, 2023)
Author's travel memories during his visit to America with reference to modern and religious education
Includes bibliographical references
Keywords: Erlebnisbericht; Reisebericht